COMPARISON OF POSTOPERATIVE PAIN WITH AND WITHOUT PECTORAL BLOCK IN PATIENTS UNDERGOING MODIFIED RADICAL MASTECTOMY - Zenab Noorain; Waqar, S H; Saad Ali Shah; Shahabul Huddah; Sajid Ali Shah (Journal of Ayub Medical College Abbottabad, 2024)
Background: Modified Radical Mastectomy is associated with significant acute postoperative pain. If this pain is not managed properly most patients will develop chronic post-mastectomy pain, which reduces quality of life. Pectoralis (PECS) block is effective in reducing pain and the consumption of analgesia in the post-operative period. The objective was to compare mean post-operative pain with or without pectoral (PECS) block in females undergoing modified radical mastectomy under general anaesthesia. Methods: A randomized controlled trial was done in the Department of General Surgery at Pakistan Institute of Medical Sciences, Islamabad. Patients who fulfilled the inclusion criteria and underwent modified radical mastectomy were included in the study. A total of 60 patients, were randomly divided into two equal groups, the PEC group and without PEC group. After surgery, patients were shifted to the postoperative care unit and were assessed for postoperative pain after 6 and 12 hours. Data was collected and descriptive analysis was done using SPSS version 22. Results: The mean age and BMI of the patients was 51.52±10.29 years and 24.1±3.94 kg/m2, respectively. Among patients from the PEC group, the mean post-op pain after the 6 hours was 2.13±0.571 while in the without PEC group, the mean post-op pain was 2.67±1.093 (p-value=0.021). Similarly, in patients from the PEC group, the mean post-op pain after the 12 hours was 1.20±0.407 while in the without PEC group, the mean post-op pain was 1.63±0.615 (p-value=0.002). Conclusion: Post-operative pain with PEC block showed significantly better control as compared to the patients without PEC block group in females undergoing modified radical mastectomy under general anaesthesia.